Appraising the Effect of the Primary Systems on the Cost Optimal Design of nZEB: A Case Study in Two Different Climates. (November 2015) - Ferrara, Maria; Fabrizio, Enrico; Virgone, Joseph; Filippi, Marco
Abstract: The work concerns the application of the cost-optimal methodology to a low-consumption French single-family house in order to study how the primary energy system influences the envelope design of a cost optimal nZEB. This is done applying a simulation based optimization method that combines TRNSYS with GenOpt in an iterative process. Four primary energy systems were considered (a gas condensing boiler, a wood boiler, an all-electrical radiator system and a combined reversible air to air heat pump) and the optimization was performed in two different French locations (Amberieu-en Bugey and Marseille).